The Impact of Non-Oil Revenue on Economic Growth: Empirical Evidence from Nigeria - Adegboyo, Olufemi Samuel; Ajoje , Olufunke; Agu, Osmond (EuroEconomica, 2023)
This study looks at the impact of non-oil revenue on Nigerian economic growth from 1981 to 2021. This study adopts endogenous growth model as its theoretical framework. The augmented Dickey Fuller test was used to determine whether each variable was stationary; the results showed that LMR is stationary at level, indicating that the series is integrated of order 0 i.e (I(0)), whereas LRGDP, LAR, LMNR, and LVATR are stationary at first difference, indicating that the series is integrated of order 1 (I(1)). ARDL is chosen for estimation since it can account for the variable's broad range of stationarity in this investigation. According to a regression estimate, agriculture, manufacturing, value-added tax, and mining all contribute to Nigeria's GDP growth. Based on these findings, Nigerian authorities should take steps to encourage local production in the non-oil sector, and the federal government of Nigeria should step up efforts to diversify the country's manufacturing sector. This is because the non-oil industry may have a significant impact on revenue. Nigeria's economic progress has been positively linked to non-oil profits, making it vital to foster and promote this sector.